Policies and finance for economic development and trade - Peter Gibbon; Caroline Hambloch; Rasmus Hundsbæk Pedersen; Ole Therkildsen (Danish Institute for International Studies (DIIS), 2014)
East Africa is undergoing a natural resource boom that has the potential to reshape national economies and development aid in the region. Questions remain whether key Danish development partners, including Tanzania, Mozambique, and Uganda, can harness newfound oil, gas, and minerals for industrial development and poverty reduction or will fall into similar 'resource curse' tarps experienced by their counterparts in West Africa. What are the challenges facing East Africa resource-rich countries? Does aid have a role to play in this new and evolving environment? How will politics serve to strengthen or weaken how natural resources can ignite development? The new DIIS report Policies and finance for economic development and trade explores these questions on natural resource development and reviews recent aid for trade initiatives.
Keywords: 300; Inequality and poverty; Land rights and investments; Oil; gas and minerals; Food and agriculture; Development policies and practice; Sub-Saharan Africa; Tanzania; Mozambique; Uganda